Sensitivity and specificity of CT colonography for the detection of colonic neoplasia after positive faecal occult blood testing: systematic review and meta-analysis. - Plumb, A; Halligan, S; Pendsé, D; Taylor, SA; Mallett, S (2014)
OBJECTIVE: CT colonography (CTC) is recommended after positive faecal occult blood testing (FOBt) when colonoscopy is incomplete or infeasible. We aimed to estimate the sensitivity and specificity of CTC for colorectal cancer and adenomatous polyps following positive FOBt via systematic review. METHODS: The MEDLINE, EMBASE, AMED and Cochrane Library databases were searched for CTC studies reporting sensitivity and specificity for colorectal cancer and adenomatous polyps. Included subjects had tested FOBt-positive by guaiac or immunochemical methods. Per-patient detection rates were summarized via forest plots. Meta-analysis of sensitivity and specificity was conducted using a bivariate random effects model and the average operating point calculated. RESULTS: Of 538 articles considered, 5 met inclusion criteria, describing results from 622 patients. Research study quality was good. CTC had a high per-patient average sensitivity of 88.8 % (95 % CI 83.6 to 92.5 %) for ≥6 mm adenomas or colorectal cancer, with low between-study heterogeneity. Specificity was both more heterogeneous and lower, at an average of 75.4 % (95 % CI 58.6 to 86.8 %). CONCLUSION: Few studies have investigated CTC in FOBt-positive individuals. CTC is sensitive at a ≥6 mm threshold but specificity is lower and variable. Despite the limited data, these results suggest that CTC may adequately substitute for colonoscopy when the latter is undesirable. KEY POINTS: • FOBt is the most common mass screening test for colorectal cancer. • Few studies evaluate CT colonography after positive FOBt. • CTC is approximately 89 % sensitive for ≥6 mm adenomas/cancer in this setting. • Specificity is lower, at approximately 75 %, and more variable. • CT colonography is a good alternative when colonoscopy is undesirable.